2020
DOI: 10.3390/polym12051046
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Nanocomposite-Based High Performance Organic Field Effect Transistor via Solution Floating Method and Mechanical Property Evaluation

Abstract: We demonstrate that using nanocomposite thin films consisting of semiconducting polymer, poly(3-hexylthiophene) (P3HT), and electrochemically exfoliated graphene (EEG) for the active channel layer of organic field-effect transistors (OFETs) improves both device performances and mechanical properties. The nanocomposite film was developed by directly blending P3HT solution with a dispersion of EEG at various weight proportions and simply transferring to an Si/SiO2 substrate by the solution floating method. The O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…The µ FET of the textile-OFET developed using the P3HT/EEG nanocomposite, as calculated from the transfer curve in Figure 10a, is 13.8 cm 2 V −1 s −1 , which is ~1.5 times amplified compared to the textile-OFET developed using a pure P3HT active channel layer (Table 1). Therefore, the electrical characteristic of amplification through EEG hybridization appears to be beneficial for the textile-OFET, as with the result of the previous research [22]. Hence, it can be concluded that the deposition of the active channel layer developed using the P3HT/EEG nanocomposite was completed successfully via the SFM, and the device developed using EEG electrodes (spray-coated EEG S/D and hot pressed EEG/textile gate electrode) operated well.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…The µ FET of the textile-OFET developed using the P3HT/EEG nanocomposite, as calculated from the transfer curve in Figure 10a, is 13.8 cm 2 V −1 s −1 , which is ~1.5 times amplified compared to the textile-OFET developed using a pure P3HT active channel layer (Table 1). Therefore, the electrical characteristic of amplification through EEG hybridization appears to be beneficial for the textile-OFET, as with the result of the previous research [22]. Hence, it can be concluded that the deposition of the active channel layer developed using the P3HT/EEG nanocomposite was completed successfully via the SFM, and the device developed using EEG electrodes (spray-coated EEG S/D and hot pressed EEG/textile gate electrode) operated well.…”
supporting
confidence: 70%
“…The SFM is a highly efficient deposition method, not only in terms of forming the well-crystalline polymer semiconductor channel in wearable devices, but also in terms of enhancing electrical properties and easily imparting new functions of the polymer semiconductor channel by combining the nanomaterials [21]. We completed the textile-OFET by applying the P3HT/EEG nanocomposite film using the SFM, which was optimized in a previous study [22] where the OFET devices fabricated using P3HT/EEG nanocomposite films with a mass ratio of 10:1 exhibited a nearly twice as high field-effect mobility compared to the OFETs developed using pristine P3HT, as well as showing an order of magnitude amplification of the OFET on-off ratio. Consequently, EEG was applied to all of the components of the textile-OFET, from the gate electrode and S/D electrodes to the active channel material.…”
Section: Resultsmentioning
confidence: 99%
“…5c). 70 Expectedly, with different temperatures and side chain lengths, graphene fillers exerted the same enhancement effect, as depicted in Fig. S13 †…”
Section: Resultsmentioning
confidence: 65%
“…Several methods for the preparation of P3HT/G nanocomposites have been reported, including solution mixing and in situ polymerization [7,8]. In situ polymerization consists of mixing nanofillers with a liquid monomer or a precursor of a low molecular weight.…”
Section: Introductionmentioning
confidence: 99%
“…Polymerization is carried out by adjusting the temperature and time. It is a very effective method that allows carbon-based nanofillers to be dispersed uniformly in the matrix, thereby providing a strong interaction between them [8]. A representative SEM image of the P3HT/G nanocomposite is shown in Figure 2.…”
Section: Introductionmentioning
confidence: 99%